Method in unit delimitation - Korpel, Marjo C. A. 1958-; Oesch, Josef M., 1943-; Porter, Stanley E., 1956- (Pericope, 2007)
In this volume selected papers from several Pericope meetings have been combined into a thematic volume, dealing with the method of unit delimitation. A hitherto unnoticed Tibero-Palestinian manuscript from Paris is discussed, as well as the text divisions in the Leviticus and Joshua Codices from the Schoyen collection and a fifth-century lectionary. The volume closes with a proposal for a new polyglot Bible, containing data with regard to unit delimitation from our traditions, Hebrew, Greek, Syriac and Latin. The Pericope Series aims at making available data on unit delimitation found in biblical and related manuscripts to the scholarly world and provides a platform for evaluating this hitherto largely neglected evidence for the benefit of biblical interpretation.